IN VITRO SENSITIVITY OF COLLETOTRICHUM ACUTATUM FROM STRAWBERRY TO FUNGICIDES WITH DIFFERENT MODES OF ACTION - Milutinović, Nađa; Stević, Milan; Vojinović, Uroš; Vasić, Tanja; Živanović, Maja; Koprivica, Staša (Journal of Agricultural Sciences (Belgrade), 2022)
Anthracnose, caused by the species Colletotrichum acutatum J.H. Simmonds, is one of the most important and devastating disease in strawberry production. The pathogen are effectively controlled by the fungicides, thus their application is necessary for achieving high yield and fruits quality. Sensitivity of 14 isolates of C. acutatum, collected from strawberry plants in Serbia, to four selected fungicides, was investigated in this study. The commercial formulation of tebuconazole, fludioxonil, prochloraz and thiophanate-methyl were used for sensitivity test. In vitro fungicide sensitivity was evaluated using mycelial growth assay method. The tested isolates were very sensitive to prochloraz and fludioxonil, with mean EC50 values of 0.067±0.062 mg L-1 and 0.093±0.043 mg L-1, respectively. Significantly higher mean EC50 values were observed for tebuconazole (1.473±0.878 mg L-1) and thiophanate-methyl (1.718±1.592 mg L-1). Toxicity of examined fungicides in mycelial growth assay of C. acutatum isolates, indicates their potential implementation in the anthracnose disease management strategy of strawberry.
Keywords: fungicide sensitivity, anthracnose, tebuconazole, fludioxonil, prochloraz, thiophanate-methyl